Including papers presented at the Sixth British Patristics Conference, Birmingham, 5-7 September 2016 - Houghton, H. A. G.; Davies, M. L.; Vinzent, Markus (Studia patristica, 2020)
This one-hundredth volume of 'Studia Patristica' includes papers from the Sixth British Patristics conference, held in Birmingham in September 2016. Thirty-seven contributions from an international range of scholars provide new studies of many of the major subjects in patristic studies, from Tertullian to Maximus the Confessor by way of Origen, John Chrysostom, Jerome and Augustine. One theme of the conference, which was held in conjunction with the European Research Council COMPAUL project, was the tradition and reception of the letters of the Apostle Paul. This is reflected in several papers, including an examination of patristic evidence for the authorship of 'Ephesians' and an analysis of exegetical techniques employed in the Greek catena tradition on 'Galatians'. Two longer contributions, by plenary speakers Frances Young and Jennifer Strawbridge, offer an extended consideration of the early Christian exegesis of particular Pauline Epistles.0